PERKEMBANGAN SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) GAJAH PUTIH DI ACEH TENGAH, 1984-2017 - Darmawan .; Mawardi .; T Abdullah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
The State Islamic High-School of Gajah Tutih a higher education institution that has been established since 1984 and continues to exist until now. The study, entitled "The Development of State Islamic High-School of Gajah Putih Takengon, Regency of Middle Aceh, 1984 to 2017" "aims to (1) know The Development of State Islamic High-School of Gajah Putih, 1984 to 2017 seen in terms of infrastructure, number of students, number of teachers, employees and others,  (2 ) knowing the factors that influenceThe Development of State Islamic High-School of Gajah Putih, 1984 to 2017, and (3) know the impact of the existence of The Development of State Islamic High-School of Gajah Putih for the surrounding community, 1984 to 2017. The study uses a qualitative approach with historical methods. The source of this research data consists of primary sources (archive data, interviews, observations) and secondary sources (reading literature). Data collection techniques are documentation, interviews and observation. Based on the results of the study it can be seen that (1) The White Elephant STAIN from 1984 to 2017 continued to develop in aspects of leadership, student affairs, lecturers of study programs, facilities and infrastructure and including the number of alumni (2) Factors that affecting The Development of State Islamic High-School of Gajah Putih Takengon is a professional teaching staff and support of the Middle Aceh Regency government, and (3) The impact of the existence of the state Islamic high-school of Gajah Tutih for the community is mainly seen in the economy marked by the opening of employment opportunities such as trading businesses, attracting good workers as permanent employees, contract and emolument.the state Islamic high-school in social field has an impact with the increasing motivation of the local community to send their family members to a higher level, in the social and cultural fields, giving birth to new scholars who contribute a lot to the lives of local people.Keywords: the state Islamic high-school of Gajah Tutih, of Middle Aceh.